Influence of silicon wafer surface roughness on semiconductor device characteristics. (26th May 2020) - Mori, Keiichiro; Samata, Shuichi; Mitsugi, Noritomo; Teramoto, Akinobu; Kuroda, Rihito; Suwa, Tomoyuki; Hashimoto, Keiichi; Sugawa, Shigetoshi
Abstract: The surface roughness of silicon wafer is one of the most important issues that degrade characteristics of semiconductor devices. The importance of spatial roughness frequency as an influential parameter has been pointed. In this research, the effect of roughness frequency on MOSFET characteristics was studied using samples with different roughness for frequency. From the obtained results, it was found that roughness with a low spatial wavelength affects electron mobility and gate insulating film reliability such as E bd, Q bd and SILC.